ON THE HISTORY OF NEOLITHIC PERIOD RESIDENCES ON THE AMUDARYA RIGHT COAST AREA (TAMADDUN NURI JURNALI, 2024)
The article analyzes the boundaries of the territory, population distribution, and geographical conditions on the right bank of the Amu Darya.